Die Nederlandse skoolidentiteitshandhawing en die betekenis daarvan vir Suid-Afrika - Rens, J. A. (Koers, 1995)
The maintaining of identity in the Netherlands and the relevance for South AfricaThis article focuses on two questions: The way in which the issue of identity has been handled in the Netherlands since the 16th century and which perspectives the history of Dutch education provides for the issue of identity in South African education in a post-apartheid dispensation. It is indicated that the process/history of maintaining the identity of the Christian school in the Netherlands was one of continuous conflict between the Christian and the neutral (secular) school. In 1920 the first phase of the conflict was resolved fairly satisfactorily with the "De Visserwet" (act), which granted parents the right to organise own schools. Since then all schools have been funded on an equal base by the state. As South Africa is currently trying to find solutions to certain educational problems, solutions resulting from the Dutch situation could possibly be applied partially to the South African situation. The main advantage would be that a variety of groups with different life views would be able to exist in harmony and to organise and support own schools receiving equal state support.